2004
DOI: 10.1039/b409514f
|View full text |Cite
|
Sign up to set email alerts
|

Selective synthesis of isomeric heterodinuclear complexes with switched metal arrangements via proton-induced reversible metal migration

Abstract: Pairs of isomeric heterodinuclear complexes, [(cod)Ir(mu-PNNN)M(L)]BF4 and [(L)M(mu-PNNN)Ir(cod)]BF4, with switched metal arrangements are prepared in a specific manner by simply changing the addition order of the reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…In the present compound, the allyl anion binds ( For comparison purpose, we investigated the CCDC-deposited mononuclear Pd complexes showing the metal with a C 3 N 2 environment, an g 3 -bound allyl ligand, a pyridine nitrogen (N py ) and an azole nitrogen (N azo ). The quest returned six entries [24]. In this set, the allyl Pd-C bond distances range from 2.073 to 2.214 Å, showing a preference for having the central Pd-C bond a little shorter than the peripheral ones.…”
Section: Resultsmentioning
confidence: 99%
“…In the present compound, the allyl anion binds ( For comparison purpose, we investigated the CCDC-deposited mononuclear Pd complexes showing the metal with a C 3 N 2 environment, an g 3 -bound allyl ligand, a pyridine nitrogen (N py ) and an azole nitrogen (N azo ). The quest returned six entries [24]. In this set, the allyl Pd-C bond distances range from 2.073 to 2.214 Å, showing a preference for having the central Pd-C bond a little shorter than the peripheral ones.…”
Section: Resultsmentioning
confidence: 99%
“…If the compound was placed under vacuum overnight 1 molecule of DME was lost. Free DME is seen in an NMR sample with DMSO-d 6 …”
Section: Dalton Transactions Papermentioning
confidence: 98%
“…In the 1 H NMR spectrum of 3 in DMSO-d 6 , the proton at the 9-position of diazafluorenide displays a singlet at 6.15 ppm, suggesting the aromaticity of the C 5 ring. If 3 is placed under vacuum overnight, the 1 H NMR showed that only 2 equiv.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…[6][7][8][9][10] In particular, the synthesis of heterometallic complexes poses significant challenges since intricate, multidentate ligandso ften lack specificity in differentiating the binding of metals. [11] Theu se of bifunctionall igandsw ith hard and soft binding sites, including those based on different P, Nand N,N-chelation, [12,13] has been as uccessful strategy in this regard; [14][15][16][17][18] however,t his approach often resultsi ns tructures that do not allow ready access to bridging coordination sites, [16][17][18][19][20] or is specific to certainm etal-metal combinations. [21] Rigid, naphthyridine-based ligands are suitable candidates for addressing these issues.…”
mentioning
confidence: 99%